Anterior Urethral Valves: Not Such a Benign Condition… - Cruz-Diaz, Omar; Salomon, Anahi; Rosenberg, Eran; Moldes, Juan M.; de Badiola, Francisco; Labbie, Andrew S.; Gosalbez, Rafael; Castellan, Miguel A. (Frontiers in Pediatrics, 2013)
Purpose: Anterior urethral valves (AUV) is an unusual cause of congenital obstruction of the male urethra, being 15 to 30 times less common than posterior urethral valves (PUV). It has been suggested that patients with congenital anterior urethral obstruction have a better prognosis than those with PUV.The long term prognosis of anterior urethral valves is not clear in the literature. In this report we describe our experience and long-term follow up of patients with AUV. Materials and methods: We retrospectively identified 13 patients who presented with the diagnosis of AUV in our institutions between 1994 and 2012. From the 11 patients included, we evaluated the gestational age, ultrasound and voiding cystourethrogram findings, age upon valve ablation, micturition pattern, creatinine and clinical follow up. Results: Between 1994 and 2012 we evaluated 150 patients with the diagnosis of urethral valves, where 11 patients (7.3%) had AUV and an adequate follow up. Mean follow up is 6.3 years. 5 patients (45.4%) had pre-natal diagnosis of AUV. The most common prenatal ultrasonographic finding was bilateral hydronephrosis and distended bladder.The mean gestational age was 37.6 weeks. Postnatally, 90% had trabeculated bladder, 80% hydronephrosis and 40% renal dysplasia. The most common clinical presentation was urinary tract infection in 5 patients (45.4%).7 patients (63.6%) had primary transurethral valve resection or laser ablation and 3 patients (27.2%) had primary vesicostomies. One boy (9.1%) had urethrostomy with urethral diverticulum excision. 2 patients (18.2%) developed end-stage renal disease (ESRD). Conclusions: Early urinary tract obstruction resulted in ESRD in 18% of our patient population. In our series, the complication rate and the evolution to renal failure are high and similar to patients with PUV. In patients with AUV we recommend long-term follow up and close evaluation of patient’s bladder and renal function.